MANAGEMENT OF THE YELLOW BOOK-BASED LEARNING PROCESS IN FORMAL ISLAMIC EDUCATION OF NAHDLATUL ULUM BOARDING SCHOOL, MAROS - Adilham, Adilham (International Journal of Technology and Education Research, 2023)
A Learning process covers all levels of education units, including Formal Diniyah Education (PDF) which is stipulated within the scope of Islamic Boarding School, as stipulated in the Regulation of the Minister of Religion of the Republic of Indonesia Number 13 of 2014 concerning Islamic Religious Education as stated in Chapter I Article I paragraph 7. The formal (PDF) formed at the Nahdlatul Ulum Islamic Boarding School is the Ulya level or equivalent to Madrasah Aliyah and there is no Wustha (Tsanawiyah) level. This class was formed in 2015 which means that approximately 5-6 batches have passed since the first year. The number of teachers is 20 people and the total number of students is 45 people. This study uses a survey research type and then presented in a qualitative descriptive manner. Data collection techniques were carried out using the interview method, in this case interviewing the PDF Principal, teachers, and students. After data collection, data analysis was then carried out by applying descriptive analysis. The yellow book-based learning management applied in the Ulya Ponpes Nahdlatul Ulum PDF Class is flexible and situational by paying attention to the ability of students to understand various reference books, so that learning management depends on the creativity of the teachers which of course must be socialized and discussed first with the Head of Madrasah regarding teaching methods, reference books, intensity of teaching hours, and others deemed necessary.